2020
DOI: 10.1002/ptr.6744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melissa officinalis (Lemon Balm) on cardio‐metabolic outcomes: A systematic review and meta‐analysis

Abstract: Recent evidence indicates a beneficial effect of Melissa officinalis (MO) intake on several chronic diseases. However, the effects of MO intake have not yet been systematically reviewed. Therefore, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of MO intake and focused on several cardiometabolic outcomes. MEDLINE, Scopus, EMBASE, Web of Science and the Cochrane Central Register of Controlled Trials were searched for MO-RCTs evaluating cardiometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…The review by Swiader et al (2019) analyzed the literature data on the chemical composition of M. officinalis and the possibilities of using it in medicine and food. Heshmati et al (2020) indicated the relationship between consumption of M. officinalis and decreased total cholesterol and reduced systolic blood pressure. Intake of M. officinalis was not observed to be related to statistically significant changes in triglycerides, low-density lipoprotein, diastolic blood pressure, high sensitivity c-reactive protein levels, fasting blood sugar, HbA1c, insulin or high-density lipoprotein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review by Swiader et al (2019) analyzed the literature data on the chemical composition of M. officinalis and the possibilities of using it in medicine and food. Heshmati et al (2020) indicated the relationship between consumption of M. officinalis and decreased total cholesterol and reduced systolic blood pressure. Intake of M. officinalis was not observed to be related to statistically significant changes in triglycerides, low-density lipoprotein, diastolic blood pressure, high sensitivity c-reactive protein levels, fasting blood sugar, HbA1c, insulin or high-density lipoprotein levels.…”
Section: Discussionmentioning
confidence: 99%
“…No serious side effects were reported. According to the study by Heshmati et al (2020), M. officinalis is safe beneficial supplement. In our experiment, addition of lemon balm to high-fat diet of rats reduced the intensity of increase in the level of triglycerides and HDL cholesterol compared with the control, and at the same time the indicator of total cholesterol, LDL cholesterol, did not change significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Using herbal medicinal agents, especially the agents with antiinflammatory properties, for conditions that lack highly effective medical treatments with lowest side effects is on the rise and has become popular among patients with chronic disorders including CVDs. [20][21][22] Although a number of antiarrhythmic medications have been identified in clinic for decades, sometimes their adverse effects particularly in long term use limit their application to some extent. 23,24 Therefore, some natural medicinal products, which might have fewer side effects, are now being utilised in arrhythmias treatment.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…18,19 Traditionally, it has been argued that M officinalis is beneficial in alleviating various conditions, for example, heart palpitation, hypertension, gastrointestinal and digestion complaints, diabetes, joint inflammation, and rheumatoid arthritis, neurological disorders, memory defects, headaches and pain, asthma, menstrual problems and bacterial, fungal or viral infections. 18,19,22,[26][27][28] Besides, M officinalis effects have been an interesting area of research in modern medicine in the last two decades. Several clinical evidences revealed improvements in depression, anxiety, sleep problems, cognition and Alzheimer's disease-associated agitation, in addition Conclusion: Together, these results seem to support the higher cardioprotective effects of MO as a medicinal plant than lifestyle modifications alone.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation